2020
DOI: 10.1089/ten.tea.2020.0033
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Human Mesenchymal Stem Cell Therapy in Incontinent Rat Injured Urethra

Abstract: Periurethral human mesenchymal stem cell (hMSC) injections are associated with functional improvement in animal models of postpartum stress urinary incontinence (SUI). However, limited data exist on the role of hMSCs in modulating gene expression in tissue repair after urethral injury. To this end, we quantified temporal gene expression modulation in hMSCs, and in injured rat urethral tissue, using RNA-seq in an animal model of SUI, over a 3-day period following urethral injury, and local hMSC injection. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…Reasons for the different outcomes might be attributed to the cell source, the culture environment in vitro, and the type of receptors. To test the hypothesis that long-term paracrine effects of hMSCs reduce inflammatory responses and modulate a healing microenvironment, Sadeghi et al (2020) performed the first all-round transcriptomic analysis of hMSC therapy for postpartum SUI. The authors observed various differentially expressed genes in the injured urethra treated with hMSCs related to several signaling pathways involved in tissue regeneration and repair, such as wound healing, vasoprotection, angiogenesis, neurogenesis, and neuroprotection as well as oxidative stress inhibition.…”
Section: Single Msc Therapy For Suimentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for the different outcomes might be attributed to the cell source, the culture environment in vitro, and the type of receptors. To test the hypothesis that long-term paracrine effects of hMSCs reduce inflammatory responses and modulate a healing microenvironment, Sadeghi et al (2020) performed the first all-round transcriptomic analysis of hMSC therapy for postpartum SUI. The authors observed various differentially expressed genes in the injured urethra treated with hMSCs related to several signaling pathways involved in tissue regeneration and repair, such as wound healing, vasoprotection, angiogenesis, neurogenesis, and neuroprotection as well as oxidative stress inhibition.…”
Section: Single Msc Therapy For Suimentioning
confidence: 99%
“…Although the feasibility of MSC therapy for SUI has been demonstrated (Kim et al, 2012;Silwal Gautam et al, 2014;Sadeghi et al, 2016;Garcia-Arranz et al, 2020;Sadeghi et al, 2020), MSCs alone may be insufficient to regenerate whole urethral components. Table 2 lists the features of MSC-based combination therapies for SUI.…”
Section: Msc-based Combination Therapymentioning
confidence: 99%
“…[5][6][7]. Stem cells are promising cells that have the potency of multidirectional differentiation and proliferation and are widely expected to be used in the field of tissue repair and regeneration [8,9]. In the muscle regeneration field, stem cells also showed vigorous potency [10].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells are promising cells that have the potency of multi-directional differentiation and proliferation and are widely expected to be used in the eld of tissue repair and regeneration. [8,9] In the muscle regeneration eld, stem cells also showed vigorous potency. [10] Various researches have devoted to verifying the mechanism of myoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%